An investigation on the therapeutic properties of novel compounds in models of asthma, inflammation and delayed type hypersensitivity - Cogan, Carina (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2000)
There are many drugs on the market for the treatment of asthma, inflammation and delayed type hypersensitivity (DTH), however few are disease modifying. The potential therapeutic effect of three novel compounds, 3C8, 6C6 and 7C9 was investigated for the treatment of these diseases. The compounds 3C8, 6C6 and 7C9 are synthetic derivatives of the natural pharmacological products, pterosin Z and acetylpterosin Z originating from the fern Pteridium aquilinium. These natural products have previously been demonstrated to inhibit calcium induced contractions in depolansed guinea-pig ileum, and histamine intestinal contractions. These observations indicated a potential therapeutic application, particularly with respect to bronchodilation and asthma. There are two forms of asthma intnnsic and extrinsic. Extnnsic asthma develops following exposure to an allergen resulting in Th2 activation, mast cell degranulation, bronchoconstnction and the influx of inflammatory cells, eosinophils and neutrophils, to the site of inflammation In contrast, intnnsic asthma results in the development of a ThI response and the development of chronic inflammation. This condition is thought to be as a consequence of a respiratory tract infection Initial in vitro studies showed the potential bronchodilatory and anti-inflammatory effect of these compounds with particular focus on asthma. 3C8 inhibited depolansed smooth muscle contractions as induced by calcium and potendy inhibited rat pentoneal mast cell degranulation as induced by compound 48/80. While 6C6 had minimal eflfect on smooth muscle contraction, 6C6 was like 3C8 a potent mast cell stabiliser. In vivo studies of asthma supported the in vitro findings. As in vivo model was set up where animals were sensitised to the antigen ovalbumin (OVA) using A10H (Th2 inducer) and freund’s complete adjuvant, containing mycobacterium tuberculosis (FCA(T); Th1 mducer), as adjuvants. 3C8 was found to prevent the late phase response to the antigen as seen by the significant reduction of breaths per minute and tidal volume as compared to untreated OVA challenged animals 3C8 also reduced the inflammatory response seen in this asthmatic model as measured by the influx of leucocytes m the bronchoalveolar lavage (BAL) fluid. This compound however had no therapeutic effect on the inflammatory asthmatic model sensitised to OVA using either AIOH (Th2 model of extnnsic asthma) or FCA(T) (Th1 model of intnnsic asthma) as separate adjuvants.
Keywords: Pharmacology, Ph.D.; Ph.D. Trinity College Dublin